Updated Japanese growth references for infants and preschool children, based on historical, ethnic and environmental characteristics - Kato, Noriko (Wiley-Blackwell, 2014)
AIM: To provide updated growth references for Japanese children from birth to 6 years of age, for use in both growth monitoring and child care. METHODS: We analysed data from two national representative surveys that provided cross‐sectional data on 3000 areas in the 2005 national census and longitudinal data from 136 hospitals. Growth references for length/height, weight, head circumference and chest circumference were constructed using the lambda‐mu‐sigma (LMS) method, with estimates of the L,M and S parameters. These updated values were then compared with growth references published by the World Health Organization. RESULTS: The 3rd, 50th and 97th smoothed percentile values of length/height, weight, head circumference and chest circumference for boys and girls from birth to 6 years are presented. The comparisons show some large differences in median measurements between the charts. CONCLUSION: Our growth references are based on a current, nationally representative sample of Japanese children. The results provide deep insight into child growth from a historical, ethnic and environmental point of view.